2004
DOI: 10.2174/1381612043383971
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Disrupting Lytic Peptides for Cancer Treatments

Abstract: Membrane disrupting lytic peptides are abundant in nature and serve insects, invertebrates, vertebrates and humans as defense molecules. Initially, these peptides attracted attention as antimicrobial agents; later, the sensitivity of tumor cells to lytic peptides was discovered. In the last decade intensive research has been conducted to determine how lytic peptides lyse bacteria and tumor cells. A number of synthetic peptides have been designed to optimize their antibiotic and anti-tumor properties and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
167
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(172 citation statements)
references
References 59 publications
3
167
1
1
Order By: Relevance
“…At present, the factors that determine differences in the efficacy and selectivity of ACPs are poorly understood, inhibiting the potential to develop these peptides as therapeutically useful anticancer agents [1,2]. However, it is generally accepted that net positive charge, hydrophobicity and amphiphilicity play major roles in the anticancer action of ACPs [1] and here, theoretical analyses are used to study the contribution of these physiochemical properties to the efficacy and selectivity of these peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the factors that determine differences in the efficacy and selectivity of ACPs are poorly understood, inhibiting the potential to develop these peptides as therapeutically useful anticancer agents [1,2]. However, it is generally accepted that net positive charge, hydrophobicity and amphiphilicity play major roles in the anticancer action of ACPs [1] and here, theoretical analyses are used to study the contribution of these physiochemical properties to the efficacy and selectivity of these peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ACP CT peptides can also show selectivity between different types of cancer cells. At present, the factors that determine these differences in efficacy and selectivity are poorly understood, limiting efforts to develop ACPs as therapeutically useful anticancer agents [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the ability to adopt a certain amphipathic secondary structure is critical to the membrane activity of a lytic peptide (3,7,10). CD spectroscopy reveals peptide structural transition during its translocation from an aqueous environment to a hydrophobic membrane-like environment.…”
Section: Random Coil To A-helixtransition Of Lytic Peptides On Enviromentioning
confidence: 99%
“…The ability to adopt certain amphipathic secondary structures is considered critical to the function of lytic peptides (3,7,10). Cyclization affects peptide behavior by imposing spatial restriction.…”
Section: Introductionmentioning
confidence: 99%
“…They serve as defense molecules against microorganisms (bacteria, fungi and viruses) especially in insects that do not possess an immune system (lymphocytes or antibodies). Despite the diversity of these peptides, they share common characteristics: positive charge, linearity, amphipathic and α-helical structure in a hydrophobic environment and rapid destruction of negatively charged membranes (Leuschner and Hansel 2004) (Figure 1). Most of these peptides are toxic to bacteria but elude normal eukaryotic cells.…”
Section: Cationic Peptidesmentioning
confidence: 99%